Takhrij and Syarah Hadith of Agrotechnology Farming as Part of Alms - Egilang Muhammad Abdilah; Wahyudin Darmalaksana; Adjat Sudrajat (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith with regard to agrotechnology. This research method is a qualitative type through literature and field studies with the takhrij and syarah hadith approaches. Results and discussion of agricultural research with several benefits, namely alms. The conclusion of this research is takhrij and syarah hadith about the recommendation of farming as part of alms.